2015
DOI: 10.3140/bull.geosci.1559
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and palaeoecology of a decapod crustacean assemblage from the Oxfordian of Stránská skála (Southern Moravia, Czech Republic)

Abstract: Primitive brachyurans and other decapods have been extensively reported from deposits of Oxfordian age, often termed microbial-sponge and coral megafacies distributed across the entirety of Europe. During the Oxfordian, coral reefs were far less common than microbial-sponge build-ups. The occurrences of decapods associated with such coral facies include those in France, Romania and the Czech Republic. Regarding the Czech Republic, the assemblage from the Stránská skála Hill has been evaluated; it is composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(43 reference statements)
0
4
0
1
Order By: Relevance
“…In many brachyurans, the hepatic region does not border the mesogastric region (e.g., Glaessner, 1969, figure 220;Davie et al, 2015, figure 71-2.6). Such mesogastric groove tubercles can be found on the internal mold and on the cuticle in representatives of Tanidromites (Starzyk, 2016(Starzyk, , 2013herein), but also in specimens of Distefania Checchia-Rispoli, 1917, Eodromites Patrulius, 1959, Gabriella Collins et al, 2006, and Pithonoton von Meyer, 1842 Gastric pits have been used extensively to describe two pits on the gastric region close to the longitudinal axis of decapods (e.g., Jakobsen and Collins, 1997;Blow, 2003;Hyzný and Müller, 2010;Klompmaker et al, 2012), but cervical pits have been used instead recently (Starzyk, 2013(Starzyk, , 2016Robin et al, 2015;Hyžný et al, 2015). We here use gastric pits because not all such pits are located clearly within the cervical groove (e.g., Dakoticancridae; Nitotacarcinus Schweitzer et al, 2007; some Etyidae) or a clear cervical groove is not always present (Paranecrocarcinidae, Zanthopsidae, some Raninoida).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many brachyurans, the hepatic region does not border the mesogastric region (e.g., Glaessner, 1969, figure 220;Davie et al, 2015, figure 71-2.6). Such mesogastric groove tubercles can be found on the internal mold and on the cuticle in representatives of Tanidromites (Starzyk, 2016(Starzyk, , 2013herein), but also in specimens of Distefania Checchia-Rispoli, 1917, Eodromites Patrulius, 1959, Gabriella Collins et al, 2006, and Pithonoton von Meyer, 1842 Gastric pits have been used extensively to describe two pits on the gastric region close to the longitudinal axis of decapods (e.g., Jakobsen and Collins, 1997;Blow, 2003;Hyzný and Müller, 2010;Klompmaker et al, 2012), but cervical pits have been used instead recently (Starzyk, 2013(Starzyk, , 2016Robin et al, 2015;Hyžný et al, 2015). We here use gastric pits because not all such pits are located clearly within the cervical groove (e.g., Dakoticancridae; Nitotacarcinus Schweitzer et al, 2007; some Etyidae) or a clear cervical groove is not always present (Paranecrocarcinidae, Zanthopsidae, some Raninoida).…”
Section: Methodsmentioning
confidence: 99%
“…Another taxon to reconsider here is Eodromites aequilatus, which Schweigert and Koppka (2011) placed in Eodromites, followed by subsequent authors (Starzyk, 2015b;Hyžný et al, 2015;Schweitzer et al, 2017Schweitzer et al, , 2018, although no detailed explanation was provided. In fact, E. aequilatus was compared to multiple morphologically similar species of Tanidromites, and it was concluded that the similarities between Eodromites and Tanidromites suggest that they are phylogenetically close (Schweigert and Koppka, 2011).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…According to Gregorová [71], the first paleontological findings were discovered during the 19th Century. In practice, all significant groups of Jurassic marine fauna are included, e.g., crinoids, cephalopods or decapods [71][72][73][74]. The talus cone profile (Quaternary sediments) offers fossils from the Pleistocene [75,76]).…”
Section: Study Areamentioning
confidence: 99%
“…17) (Fraaije et al 2006Nyborg et al 2009: fig. 4) or fossil Retropluma Gill, 1894(Hyžný et al 2015Gašparič & Križnar 2017: fig. 3B;Gašparič et al 2019: fig.…”
Section: Icriocarcinidae šTevčić 2005unclassified